Behavioral finance psychology, decision-making, and markets - Ackert, Lucy F.; Deaves, Richard (Mason, Ohio South-Western Cengage Learning, 2010)
"This comprehensive text--ideal for your behavioral finance elective-- links finance theory and practice to human behavior. The book begins by building upon the established, conventional principles of finance that students have already learned in their principles course. The authors then move into psychological principles of behavioral finance, including heuristics and biases, overconfidence, emotion and social forces. Students learn how human behavior influences the decisions of individual investors and professional finance practitioners, managers, and markets. Your students gain a strong understanding of how social forces impact people's choices. The book clearly explains what behavioral finance indicates about observed market outcomes as well as how psychological biases potentially impact the behavior of managers. Students learn the implications of behavioral finance on retirement, pensions, education, debiasing, and client management. This book is unique as it spends a significant amount of time examining how behavioral finance can be used effectively by practitioners today."--Provided by publisher.
Keywords: Investments -- Psychological aspects; Investments -- Decision making